2020
DOI: 10.5194/acp-20-12697-2020
|View full text |Cite
|
Sign up to set email alerts
|

Vertical variability of the properties of highly aged biomass burning aerosol transported over the southeast Atlantic during CLARIFY-2017

Abstract: Abstract. Seasonal biomass burning (BB) from June to October in central and southern Africa leads to absorbing aerosols being transported over the South Atlantic Ocean every year and contributes significantly to the regional climate forcing. The vertical distribution of submicron aerosols and their properties were characterized over the remote southeast Atlantic, using airborne in situ measurements made during the CLoud-Aerosol-Radiation Interactions and Forcing for Year 2017 (CLARIFY-2017) campaign. BB aeroso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(134 citation statements)
references
References 102 publications
17
116
1
Order By: Relevance
“…The size distributions for BBA from Peers et al (2019) and Wu et al (2021) are consistent with those determined from SAFARI-2000, although Haywood et al (2003) chose to describe the accumulation mode with two log-normal distributions rather than a single log-normal distribution. The corresponding refractive indices retrieved over the CLAR-IFY period (16 August-7 September 2017) derived from AERONET Version 2 algorithms for the Ascension Island site are 1.47-0.020i at a wavelength of 550 nm.…”
Section: Analysis Of Aerosol Size Distributionsmentioning
confidence: 71%
See 2 more Smart Citations
“…The size distributions for BBA from Peers et al (2019) and Wu et al (2021) are consistent with those determined from SAFARI-2000, although Haywood et al (2003) chose to describe the accumulation mode with two log-normal distributions rather than a single log-normal distribution. The corresponding refractive indices retrieved over the CLAR-IFY period (16 August-7 September 2017) derived from AERONET Version 2 algorithms for the Ascension Island site are 1.47-0.020i at a wavelength of 550 nm.…”
Section: Analysis Of Aerosol Size Distributionsmentioning
confidence: 71%
“…Thus, in general, the aerosol at lower altitudes can be significantly older compared to that located at elevated altitudes (see analysis of ORACLES data by Dobracki et al, 2021). There is clear evidence from both Wu et al (2021) and Dobracki et al (2021) that aerosol higher up in the residual CBL exhibits a higher SSA (i.e. it is less absorbing on a per particle basis) than that lower down.…”
Section: Vertical Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between the top-of-cloud reflectance and the COT is convex, which means that the COT derived from the mean reflectance of a pixel is smaller than the COT calculated from the mean COTs within the pixel. Zeng et al (2012) have shown that subpixel inhomogeneities cause satellite sensors with a coarser spatial resolution, such as SEVIRI, to retrieve a smaller COT. Also, as the clouds becomes thicker, the visible and the near-infrared (NIR) measurements become less sensitive to the COT for both instruments.…”
Section: Statistical Comparisonsmentioning
confidence: 99%
“…A number of field campaigns—including Dynamics‐Aerosol‐Chemistry‐Clouds Interactions in West Africa (DACCIWA), Aerosols, Radiation and Clouds in southern Africa (AEROCLO‐sA), Layered Atlantic Smoke Interactions with Clouds (LASIC), ObseRvations of Aerosols above CLouds and their intEractionS (ORACLES), and Cloud and Aerosols Radiative Impact and Forcing (CLARIFY)—have recently been carried out over the eastern Atlantic Ocean, with the aim to better quantify the BBA radiative effects (Flamant, Knippertz, et al, 2018; Formenti et al, 2019; Zuidema et al, 2016, 2018). Both in situ and remote‐sensing observations acquired during these campaigns have all emphasized a strong shortwave (SW) absorption (low single scattering albedo, SSA ) in BBA transported from the coast of southern Africa to the far north over southern West Africa (SWA) (Chylek et al, 2019; Denjean et al, 2020; Pistone et al, 2019; Wu et al, 2020; Zuidema et al, 2018). This means that BBA over this climatically important region is more absorbing than is currently represented in climate models (Mallet et al, 2019; Peers et al, 2016; Stier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%